2011
DOI: 10.1187/cbe.10-07-0085
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Project-Based Molecular Biology Laboratory Emphasizing Protein Structure–Function Relationships in a Large Introductory Biology Laboratory Course

Abstract: In introductory laboratory courses, many universities are turning from traditional laboratories with predictable outcomes to inquiry-inspired, project-based laboratory curricula. In these labs, students are allowed to design at least some portion of their own experiment and interpret new, undiscovered data. We have redesigned the introductory biology laboratory course at Brandeis University into a semester-long project-based laboratory that emphasizes concepts and contains an element of scientific inquiry. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
1
22
0
1
Order By: Relevance
“…Past and current evidence have suggested that the majority of our students learned little of the above when performing cookbook laboratories (7,11,27). Upon review of our assessments as evaluated by Bloom's taxonomy, we also found that our laboratory assignments did not require higher-level or critical thought and thus needed revision (19).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Past and current evidence have suggested that the majority of our students learned little of the above when performing cookbook laboratories (7,11,27). Upon review of our assessments as evaluated by Bloom's taxonomy, we also found that our laboratory assignments did not require higher-level or critical thought and thus needed revision (19).…”
mentioning
confidence: 82%
“…Unfortunately, this evolution to increased content coverage and more structured experiments for majors in the course lecture and laboratory does not produce learning gains to match our aspirations (11,18,21). Nor does this inspire creativity, flexibility, and inquisitiveness in our students or help them develop deeper critical and integrative thinking skills (7,8,22,23,27).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Students participate in the experimental design process, creating their own individual mutant proteins (Treacy et al, 2011). The results of these student-led projects are unknown.…”
mentioning
confidence: 99%
“…The main purpose this learning is to enable students to practice what they learn by integrating theory and practice. Furthermore, students can develop their creative thinking skills to solve life and environmental challenges later (Yilmaz and Cavas, 2007;Holubova, 2008;Yalcin, Turgut, and Büyükkasap, 2009;Bell, 2010;Eskrootchi and Oskrochi, 2010;Treacy, 2011;Bjorner, Kofoed and Pederson, 2012;Lou et al, 2012;Hsieh, Lou and Shih, 2013;Robinson, 2013;and Husamah, 2015).…”
Section: Introductionmentioning
confidence: 99%